Exponential Function of a bounded Linear Operator on a Hilbert Space. - Baghdad Science Journal (Baghdad Science Journal, 2014)
In this paper, we introduce an exponential of an operator defined on a Hilbert space H, and we study its properties and find some of properties of T inherited to exponential operator, so we study the spectrum of exponential operator e^T according to the operator T.